2013
DOI: 10.1055/s-0033-1341588
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional Evaluation of Unilateral Cleft Rhinoplasty Results

Abstract: Three-dimensional (3D) imaging is a relatively new method of objectively evaluating surgical results, allowing the surgeon to accurately measure postsurgical changes with little inconvenience to the patient. Its accuracy and reliability has been consistently demonstrated in the literature. This article describes updated methods that we use with 3D imaging software to assess rhinoplasty results at our institution. The measurements described include the assessment of symmetry, tip projection, rotation, volume, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 7 publications
0
24
0
1
Order By: Relevance
“…Newer 3-dimensional stereophotogrammetry technology provides the surgeon a powerful tool to objectively quantify shape, length, and volume changes accomplished via rhinoplasty. [1][2][3] Digital image morphing should be considered, as it improves the surgeon's ability to communicate with their patients preoperatively on prospective changes to the nose. Function should never be compromised for aesthetics.…”
Section: Preoperative Planning and Preparationmentioning
confidence: 99%
“…Newer 3-dimensional stereophotogrammetry technology provides the surgeon a powerful tool to objectively quantify shape, length, and volume changes accomplished via rhinoplasty. [1][2][3] Digital image morphing should be considered, as it improves the surgeon's ability to communicate with their patients preoperatively on prospective changes to the nose. Function should never be compromised for aesthetics.…”
Section: Preoperative Planning and Preparationmentioning
confidence: 99%
“…Portable 3D handheld scanners are now available that allow capturing 3D models of the human body by moving the scanner around the region of interest to acquire its entire surface. These compact, non-invasive systems have the potential to acquire the patient specific 3D head shape to quantify surgical outcomes in the operating theatre and monitor follow-up results [8][9][10][11] during clinics in craniofacial applications.…”
Section: Introductionmentioning
confidence: 99%
“…The guides are easy to use and can be applied without extensive midface exposure. The results of this study have shown that the proposed technique achieved a satisfactory precision and accuracy in positioning the maxilla with an acceptable small RMSD of less 0.5 [22,23]. The color-scaled visualization indicated a clinically acceptable superimposition discrepancy between the virtual surgical planning and the postsurgical images (Fig.…”
Section: Discussionmentioning
confidence: 62%
“…9). An RMSD value of 0.5 or less is considered to be clinical acceptable accuracy of surgical simulation and postoperative alignment [22,23]. Each manual superimposition was performed twice by two observers to investigate the intraobserver reproducibility and Left before screw fixation, right after screw fixation interobserver reliability.…”
Section: Outcome Assessmentmentioning
confidence: 99%